Damage Identification of Wind Turbine Blades Using Piezoelectric Transducers - Seong-Won Choi; Kevin M. Farinholt; Stuart G. Taylor; Abraham Light-Marquez; Gyuhae Park (Shock and Vibration)
This paper presents the experimental results of active-sensing structural health monitoring (SHM) techniques, which utilize piezoelectric transducers as sensors and actuators, for determining the structural integrity of wind turbine blades. Specifically, Lamb wave propagations and frequency response functions at high frequency ranges are used to estimate the condition of wind turbine blades. For experiments, a 1 m section of a CX-100 blade is used. The goal of this study is to assess and compare the performance of each method in identifying incipient damage with a consideration given to field deployability. Overall, these methods yielded a sufficient damage detection capability to warrant further investigation. This paper also summarizes the SHM results of a full-scale fatigue test of a 9 m CX-100 blade using piezoelectric active sensors. This paper outlines considerations needed to design such SHM systems, experimental procedures and results, and additional issues that can be used as guidelines for future investigations.